Patterns of combustible and electronic cigarette use during pregnancy and associated pregnancy outcomes - Regan, Annette; Pereira, Gavin (NATURE RESEARCH, 2021)
Although pregnant smokers may perceive electronic cigarettes (e-cigarettes) as safe alternatives to smoking combustible cigarettes, few studies have evaluated perinatal e-cigarette use and its associated health effects. We analyzed data from the Pregnancy Risk Assessment Monitoring System (PRAMS, 2016–2018) for 16,022 women who recently gave birth and reported smoking combustible cigarettes prior to pregnancy. Using average marginal predictive values from multivariable logistic regression to produce adjusted prevalence ratios (aPRs), we estimated the prevalence of combustible cigarette smoking during pregnancy and adverse birth outcomes associated with e-cigarette use. In total, 14.8% of smoking women reported using e-cigarettes prior to pregnancy. There was no association between e-cigarette use prior to pregnancy and combustible cigarette smoking during pregnancy (aPR 0.95; 95% CI 0.88, 1.02); however, e-cigarette use during pregnancy was associated with higher prevalence of combustible cigarette smoking during pregnancy (aPR 1.65; 95% CI 1.52, 1.80). In this sample, we did not observe evidence to support reduced risk of preterm birth, small-for-gestational age and low birthweight compared to combustible cigarette smoking during pregnancy. The prevalence of LBW was higher for those who used e-cigarettes, even exclusively, compared to women who quit smoking cigarettes entirely. These results suggest that e-cigarettes should not be considered a safe alternative to combustible cigarette smoking during pregnancy.